KEMAMPUAN AWAL PESERTA DIDIK: PENGERTIAN, KEGUNAAN IDENTIFIKASI,TEKNIK MENDETEKSI, DAN JENIS-JENISNYA DALAM PERSPEKTIF TEORITIS DAN PRAKTIS - Agis Ayuningtias; Puteri Mayla Ramzhi; A’lal Aqil; M. Yunus Abu Bakar (JIP: Jurnal Ilmu Pendidikan, 2026)
Students’ prior knowledge is the cognitive foundation that determines how effectively new learning can be received, processed, and integrated. This article comprehensively examines four main aspects: (1) the definition of students’ prior knowledge from various expert perspectives; (2) the benefits of identifying prior knowledge in educational practice; (3) techniques for detecting prior knowledge; and (4) the types of prior knowledge that educators need to understand. This article integrates insights from Wulandari, Wardah, Syarifah and Bakar (2024), Wardah, Wulandari, Nurirrohman and Bakar (2025), Firmansyah, Ramadhani, Al Ghifari and Bakar (2026), Bakar, Salsabila, Furqon and Kabir (2025), and Kustianing, Saiban, Pangarsa and Bakar (2021) to present a unified framework for understanding and utilizing prior knowledge in instructional design. The findings confirm that prior knowledge functions as a mandatory prerequisite that determines the direction and quality of the entire learning process, and educators who systematically identify and respond to it are better equipped to design effective and meaningful learning experiences.